Annual Plan, 1987-88 Orissa (Draft) - Planning Commission (Planning Commission, 1986)
The Annual Plan for 1987-88, which is the mid-year of the Seventh Plan, is crucial both for the appraisal of the past performance as well as reassessment of the prospects and priorities for the remaining period of the plan. While the Plan targets in vital areas like agriculture, rural development, drinking water-supply etc. may be achieved in adequate measure, special steps may still be necessary for improved performance and infrastructure development in some other areas. The emphasis in the Annual Plan, 1987-88, is on examining the economy’s capacity to adjust to the new requirements and identifying appropriate strategies and policy-packages to achieve the Plan objectives. This would provide a firm basis for growth during the Plan and the post-plan periods.
Government of Orissa